The role of research laboratory in developing skilled human capital: Lessons learned from Malaysian and Japanese Universities / Atiqurrahman Rosdi - Atiqurrahman, Rosdi (2019)
Rapid advancement of the economic trend nowadays requires multi-skilled graduates to fulfil the labour market demands. This scenario denotes high quality graduates in the field of Science, Technology, Engineering and Mathematics (STEM) that could satisfy the needs for quality trained researchers and graduates in Malaysia. Looking at the developed eastern country, Japan is renowned as one of the worlds’ fastest developing technological inventors even though it had been devastated with an atomic bomb in 1945. Strong research capacity in the Japanese laboratory has been recognized as an indicator for the advanced development in Japan. Concerning the significant role of research laboratory, it could contribute towards the development of new knowledge, human values, research skills, management settings, and social networks. Hence, this study examines the practices of research laboratory in university to develop skilled human capital in science and technology in Malaysia and Japan. It provides an overview of capacity building of research laboratory in producing practical skills, transferable skills and intellectual simulation especially in the context of 21st century learning in Malaysia and Japan. This study was completed through an original case study, interviews and short visit that were conducted in Malaysia, i.e. University of Malaya (UM), University of Putra Malaysia (UPM), National University of Malaysia (UKM), UCSI University and Japan, i.e. Kyoto University, Tsukuba University, Kyushu University, and Japan Advanced Institute of Science and Technology (JAIST). The analysis presents key findings of historical development, science and technology strength in research and development, support for research, research culture, positioning student to a research group, mentor-apprenticeship, monitoring students’ development, and networks and output. In order to adopt the best practice in research laboratory for human capital growth, laboratory research universities must function in a supportive physical and intellectual infrastructure. This study also suggests that research design should expose students to the real research world in parallel to the global interest to develop the life-long skills and provide collaborative interaction between different institutions like the university, industry, and government. The analysis would be helpful to improve the performance of research laboratories in universities.